Urban and Peri-Urban Farming : Some Insights from a Developed Nation - Sikdar, Samrat (Journal of Agricultural Extension Management, 2023)
Rapid urbanisation is prominent in various parts of the world. This is an evident outcome of the overgrowing world population, and it also threatens the future food production system. This world needs more and more food items to feed its habitants. But unfortunately, food production does not show a directly proportional relation with the phenomenon of rapid urbanisation. It compels the scientists to think more about the urban and Peri-Urban Agriculture (UPA). UPA is getting much more attention nowadays, as it allows to grow the food items in urban as well as peri-urban areas. The main objective of this paper is to provide an overview of the UPA, including the possible existing barriers and challenges. There are the several ways to grow food items through UPA, but most of the available academic literatures did not focus significantly on the different existing barriers of this UPA. In this paper, the possible barriers of UPA have been divulged through the unstructured literature review of a bunch of previous excellent studies on UPA in the United States, alongside the different UPA project types as well as approaches. Lack of clear agri-inclusive ordinances is a valid problem towards implementing UPA, alongside zoning difficulties and limited access to land. The growing expenditures of the farmers as a part of UPA farming is also an issue or concern which rather exacerbated with no/very low funding opportunities. Reluctance of the farmers in attending the various farmers’ training program is also a barrier here alongside the difficulty of the certification system. Smooth accessibility to the irrigation water and also the management strategy for the water run-off are the challenging tasks as indicated by urban farmers & planners. Insurance coverage is very limited in case of UPA which is also one of the solid challenges as faced by urban growers